Optimalisasi Fungsi Inspektorat dalam Pengawasan Keuangan Daerah di Kabupaten Kepulauan Talaud - Matei, Angela Mulyani; Karamoy, Herman; Lambey, Linda (Universitas Sam Ratulangi, 2017)
Abstract. The function of supervision by Inspectorate is crucial to ensure the management of local government is running effectively and efficiently. As the internal supervisor institution, Inspectorate should be able to optimize its functions based on The Rule of Minister of Home Affairs Number 64/2007 to create the good governance and clean government. This study is aimed to (1) determine the optimilising the function of Inspectorate in Talaud Island Municipality; (2) analyse the obstacles in optimilising the function of Inspectorate in Talaud Island Municipality; (3) analyse the strategies to optimize the function of Inspectorate in supervising local finance. This study is an exploratory qualitative research. Data were collected by in-depth interviews, observation, and study documentation from primary data and secondary data. The results show the function of Inspectorate in supervising local finance in Talaud Island Municipality is not optimal yet. It is, thus, strategies are required to overcome the obstacles in supervision of local finance by Inspectorate of Talaud Island Municipality. Strategies consist of to: (1) increase the quantitiy of inspector/audit staff; (2) increase of auditor competencies; (3) increase the allocation of supervision budget; (4) increase of facility supervision; (5) optimize the rule of internal auditor as consultant and catalyst; (6) punishment to local work unit (SKPD) staff who are not committed to conduct supervision; and (7) joint commitment of local government in supervision field. Keywords : supervision, optimilising, local finance, the rule of minister of home affairs number 64/2007 Abstrak. Fungsi Pengawasan Inspektorat sangat penting dalam menjamin penyelenggaraan pemerintahan daerah yang efektif dan efisien. Inspektorat sebagai lembaga pengawas internal pemerintah daerah harus mampu melaksanakan fungsinya berdasarkan Permendagri No. 64 Tahun 2007 secara optimal untuk mewujudkan tata kelola pemerintahan yang baik dan bersih. Penelitian ini bertujuan untuk : (1) mengetahui apakah fungsi Inspektorat Kabupaten Kepulauan Talaud sudah optimal;Â (2) menganalisis kendala-kendala yang dihadapi Inspektorat Kabupaten Kepulauan Talaud dalam optimalisasi fungsi pengawasan keuangan daerah; (3) menganalisis upaya atau strategi Inspektorat Kabupaten Kepulauan Talaud dalam mengoptimalkan fungsi pengawasan keuangan daerah. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan eksploratori. Pengumpulan data dilakukan melalui wawancara, observasi dan studi dokumentasi yang bersumber dari data primer dan data sekunder. Hasil penelitian ini menunjukkan fungsi Inspektorat dalam pengawasan keuangan daerah di Kabupaten Kepulauan Talaud belum optimal, sehingga dibutuhkan strategi untuk mengatasi kendala-kendala dalam pelaksanaan fungsi pengawasan yakni (1) penambahan tenaga pengawas; (2) meningkatkan kompetensi APIP; (3) meningkatkan alokasi anggaran pengawasan; (4) penambahan fasilitas pengawasan; (5) mengoptimalkan peran APIP sebagai konsultan dan katalis; (6) pemberian sanksi tegas bagi SKPD yang lalai atau kurang berkomitmen terhadap pelaksanaan pengawasan; dan (7) adanya komitmen bersama pemerintah daerah dalam bidang pengawasan. Kata kunci: pengawasan, optimalisasi, keuangan daerah, Permendagri No. 64 Tahun 2007 Â